NEW DISCOVERIES IN DYNAMICS OF AN M8 EARTHQUAKE-PHENOMENA AND THEIR IMPLICATIONS FROM THE 2003 TOKACHI-OKI EARTHQUAKE USING A LONG TERM MONITORING CABLED OBSERVATORY - Mikada H.; Mitsuzawa K.; Watanabe T.; Morita S.; Matsumoto H.; Sugioka H.; Baba T.; Araki E.; Otsuka R.; Suyehiro K. (My University, 2006)
At the 2003 Tokachi-oki earthquake of M8, seafloor phenomena such as a generation process of tsunami, seafloor uplifts, turbidity current, etc., were observed using a cabled observatory installed on the seafloor. The turbidity current was observed as a benthic storm caused presumably by the mainshock. The seafloor uplifts were observed at the mainshock and continuously after the mainshock. The uplifts were 0.35, 0.37, and 0.12 m for epicentral distances of 25.5, 31.4, and 81.7 km, respectively. After the mainshock, a continuous uplift of the seafloor is observed at all three pressure gauge locations indicating that there was a change in the state of friction on the plate boundary interface by the mainshock. In this paper, we first show what was observed using the cabled observatory installed right above the focal area of the earthquake, and then we discuss to summarize these phenomena associated with the earthquake, its possible causes, and future directions in long term monitoring of seismogenic processes. © 2006 Elsevier B.V. All rights reserved.
Keywords: 2003 TOKACHI-OKI EARTHQUAKE; COSEISMIC TURBIDITY CURRENT; EARTHQUAKE PRECURSORY; PRESSURE GAUGE; REAL-TIME CABLED OBSERVATORY; SEAFLOOR GEODESY